Indian Basic Structure Jurisprudence in the Islamic Republic of Pakistan: Reconfiguring the Constitutional Politics of Religion. Issue 2 (3rd December 2018) - NELSON, Matthew J
Abstract: In both India and Pakistan, parliament is constitutionally endowed with 'constituent power', that is, the power to introduce constitutional amendments via procedures laid down in the constitution itself. Duly promulgated amendments, however, are occasionally struck down when Supreme Court judges see them as violating what the judges themselves define as the 'essential features' of each country's constitutional 'basic structure'. I trace the migration of basic structure jurisprudence from India to Pakistan, focusing on the ways in which it has elevated the power of judges over that of elected officials in the realm of religion-state relations. Specifically, I highlight the ways in which judicial independence vis-à-vis judicial appointments has been described as an essential feature of each country's constitution, greatly enhancing the autonomous power of judges to mould constitutional benches that, in turn, define India's constitutional understanding of secularism and Pakistan's relationship with Islam.